The Role of Pneumococcal Virulence Factors in Ocular Infectious Diseases - Angela H. Benton; Mary E. Marquart (Interdisciplinary Perspectives on Infectious Diseases)
Streptococcus pneumoniae is a gram-positive, facultatively anaerobic pathogen that can cause severe infections such as pneumonia, meningitis, septicemia, and middle ear infections. It is also one of the top pathogens contributing to bacterial keratitis and conjunctivitis. Though two pneumococcal vaccines exist for the prevention of nonocular diseases, they do little to fully prevent ocular infections. This pathogen has several virulence factors that wreak havoc on the conjunctiva, cornea, and intraocular system. Polysaccharide capsule aids in the evasion of host complement system. Pneumolysin (PLY) is a cholesterol-dependent cytolysin that acts as pore-forming toxin. Neuraminidases assist in adherence and colonization by exposing cell surface receptors to the pneumococcus. Zinc metalloproteinases contribute to evasion of the immune system and disease severity. The main purpose of this review is to consolidate the multiple studies that have been conducted on several pneumococcal virulence factors and the role each plays in conjunctivitis, keratitis, and endophthalmitis.